Alterations in Lysosome Homeostasis in Lipid-Related Disorders: Impact on Metabolic Tissues and Immune Cells - Cabrera-Reyes, Fernanda; Parra-Ruiz, Claudia; Yuseff, María Isabel; Zanlungo, Silvana (Frontiers in Cell and Developmental Biology, 2021)
Lipid-related disorders, which primarily affect metabolic tissues, including adipose tissue and the liver are also associated with alterations in lysosome homeostasis. Obesity is one of the more prevalent diseases, which results in energy imbalance within metabolic tissues and lysosome dysfunction. Less frequent diseases include Niemann-Pick type C (NPC) and Gaucher diseases, both of which are known as Lysosomal Storage Diseases (LSDs), where lysosomal dysfunction within metabolic tissues remains to be fully characterized. Adipocytes and hepatocytes share common pathways involved in the lysosome-autophagic axis, such as the function of cathepsins and CD36, an immuno-metabolic receptor, which are altered in lipid diseases and thereby impact metabolic functions. In addition to intrinsic defects observed in metabolic tissues, cells of the immune system, such as B cells can infiltrate adipose and liver tissues, during metabolic imbalance favoring inflammation. Moreover, B cells rely on lysosomes to promote the processing and presentation of extracellular antigens and thus could also present lysosomal dysfunction and affect such functions. On the other hand, growing evidence suggests that cells accumulating lipids display defective inter-organelle membrane contact sites (MCSs) established by lysosomes and other compartments, which contribute to metabolic dysfunctions at the cellular level. Overall, in this review we will discuss recent findings addressing common mechanisms that are involved in lysosome dysregulation in adipocytes and hepatocytes during obesity, NPC, and Gaucher diseases. We will discuss whether these mechanisms may modulate the function of B cells and how inter-organelle contacts, emerging as relevant cellular mechanisms in the control of lipid homeostasis, have an impact on these diseases.